Cerâmica vermelha, concreto autoclavado e composito a partir de concreto autoclavado e cimento branco como substrato em wetlands construídos tratando matéria carbonácea, nutrientes e hormônios - Silva, Lucas de Carvalho (2023)
The use of a substrate with sorption capacity and macrophytes capable of removing macro and micronutrients can contribute to the removal of pollutants and the development of microbial communities, favoring wastewater treatment by constructed wetlands (CW). The objective of this research was to evaluate the use of waste from red ceramics (RC, fragments of bricks), autoclaved aerated concrete (AC), and the composite generated from chemically activated AC with white cement (AAC) as a substrate in vertical subsurface flow constructed wetlands with saturated bottom (VCW) in the removal of carbonaceous, nitrogenous, phosphate matter and endocrine disruptors (ED). The three systems were operated in three stages with varying sampling times: Stage I of 24 h, Stage II of 48 h, and Stage III of 48 h, with the addition of endocrine disruptors (E1, E2, and EE2), totaling 380 days of operation. In Stage III, CW-RC showed better efficiency in the removal of COD (91%), NO2- (85%), and NO3- (94%). No significant difference (p-value > 0.05) was observed in the removal of TKN (31%, 33%, and 27%) and N-Ammon (0%, 10%, and 0%) between Stages I, II, and III, nor between Stages II (85%) and III (77%) for PT removal. CW-AC and CW-AAC presented better results for TKN removal (70% and 66%), N-Ammon removal (70% and 62%), and PT removal (95% and 92%) in Stage II. In CW-AC, better removal of COD was observed in Stage II (84%), and better NO2- was observed in Stage III (87%). No significant difference (p-value > 0.05) was observed in the removal efficiency of NO3- between Stages II (89%) and III (85%). CW-AAC showed better removal of NO2- (93%) and NO3- (76%) in Stage III. No significant difference (p-value > 0.05) was observed in the removal of COD between Stages II (78%) and III (81%). Stage II proved to be more effective in the behavior of CW-AC and CW-AAC systems, possibly due to more significant interaction between macrophytes, substrate, and microorganisms. It can be concluded that the systems maintained operational stability and improved denitrification performance after adding Eds. In the evaluation of the microbial community structure of the system, Firmicutes, Proteobacteria, and Planctomycetes were the most abundant phyla. In addition, Anammox bacteria were identified, such as Candidatus brocadia and Candidatus Jettenia, and some responsible for the degradation of Eds, such as Pseudomonas, Citrobacter, and Comamonas. In the mass balance after 188 days of operation, it was observed that CQA (258.5 g m-2 b-1) showed higher PT retention capacity, while CV (246.4 g m-2 b-1) retained more NT. The macrophyte contributed with a maximum removal of 5.4% for PT and 7.0% for NT.